2010
DOI: 10.1161/circulationaha.110.966333
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Pulseless Electric Activity Versus Ventricular Fibrillation

Abstract: Background— Corresponding with a continuing decline in the prevalence of sudden cardiac arrest cases presenting with ventricular fibrillation (VF), there has been a significant rise in the prevalence of pulseless electrical activity (PEA). Given significantly lower survival from PEA versus VF, we comprehensively investigated PEA correlates by incorporating first-responder data with lifetime clinical history information. Methods and Results— … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
74
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 93 publications
(82 citation statements)
references
References 35 publications
6
74
1
1
Order By: Relevance
“…Several studies have shown that women are significantly more likely than men to manifest PEA. [45][46][47] In the Oregon SUDS, approximately one third of women presented with PEA, 45 and after adjustment for demographics, Utstein data elements, and disease burden, female sex remained a significant predictor of PEA (OR, 1.48; 95% CI, 1.05-2.09). 48 However, women appear to have a survival advantage over men for SCA resuscitation outcomes.…”
Section: Risk Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have shown that women are significantly more likely than men to manifest PEA. [45][46][47] In the Oregon SUDS, approximately one third of women presented with PEA, 45 and after adjustment for demographics, Utstein data elements, and disease burden, female sex remained a significant predictor of PEA (OR, 1.48; 95% CI, 1.05-2.09). 48 However, women appear to have a survival advantage over men for SCA resuscitation outcomes.…”
Section: Risk Factorsmentioning
confidence: 99%
“…44 In addition, an analysis from the Oregon Sudden Unexpected Death Study (Oregon SUDS) showed that older age was a significant predictor of future PEA after adjustment for other demographic variables, arrest circumstances, and comorbidities. 45 Sex is also associated with the presenting arrhythmia during SCA. Several studies have shown that women are significantly more likely than men to manifest PEA.…”
Section: Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In other studies, there has been an unexplained continuing decline in the prevalence of sudden cardiac arrest cases presenting with ventricular fibrillation and corresponding rise in the prevalence of pulseless electrical activity (PEA) arrests. 4 The 7 patients who had an initial cardiac rhythm of PEA and were judged to have died of an arrhythmia were all, except 1, off cardiac monitoring. Four had myocardial infarctions, 3 heart block pre-arrest, 1 postoperative intramyocardial hematoma, 1 myocardial metastatic melanoma, 1 acute heart transplant rejection, and 3 ventricular tachycardia or fibrillation following PEA, suggesting that PEA was a phase in the evolution of an arrhythmogenic death.…”
Section: Discussionmentioning
confidence: 99%
“…A substantial proportion of sudden cardiac arrests, approximately half in a recent study,2 are associated with ventricular tachycardia (VT) or ventricular fibrillation (VF). It has been observed clinically that sustained VT and VF are often preceded by several irregularly timed premature complexes,3, 4 and studies conducted to explore this phenomenon have shown that specific coupling interval patterns of premature complexes, such as short‐long‐short5 and short‐short‐short,6 tend to lead to reentry and VT.…”
Section: Introductionmentioning
confidence: 99%